FAKTOR YANG MEMPENGARUHI KESESUAIAN IMPLEMENTASI DENGAN RENCANA TATA BANGUNAN DAN LINGKUNGAN DALAM PROGRAM PENATAAN LINGKUNGAN PERMUKIMAN BERBASIS KOMUNITAS STUDI KASUS: DESA JENDI WONOGIRI - Antissia Meuthia Rizky; Winny Astuti; Galing Yudana (ARSITEKTURA, 2015)
Jendi village, selected as a pilot project which received the Neighborhood Development program (ND) is the government's effort to solve the poor’s problemsbased onimprovementof housing’s quality. To achieve the goal, the building implementation should be based on the plan that has been made. So, it makes a question “is the implementation of Jendi Village based on Building and Environmental Planning and how the factors affect the suitability itself.”This research uses quantities research methods to analyze the factors that affect the implementation of RTBL Jendi Village. The suitability is found from the analysis which compare the plan and the implementation related with each aspect of planning. To know the factors that affect the implementation of RTBL Jendi Village, the analysis is done using the quantities methods from combination of implementable suitability and the suitable factors of implementation.  The research obtain that the implementable suitability with RTBL of Jendi Village has 81,25% with the suitability from streets, public open space, environment identity concept, the face of the streets, drainage. Factors that affect the implementable suitability with RTBL Jendi Village is communication, human resource, authority, infrastructures and facilities, money, attitude and commitment, bureaucracy structures, and support. And the other factor which not affected with suitability is information resource.Keywords: Factor that affect the implementable suitability, RTBL, Neighborhood Development